Genome-wide association study identifies five loci associated with susceptibility to pancreatic cancer in Chinese populations - Wu, Chen; Miao, Xiaoping; Huang, Liming; Che, Xu; Jiang, Guoliang; Yu, Dianke; Yang, Xianghong; Cao, Guangwen; Hu, Zhibin; Zhou, Yongjian; Zuo, Chaohui; Wang, Chunyou; et al. (Nature genetics, 2012)
Dongxin Lin and colleagues report a genome-wide association study for pancreatic cancer in Chinese populations. The authors identify five new genetic loci associated with risk of pancreatic cancer. Pancreatic cancer has the lowest survival rate among human cancers, and there are no effective markers for its screening and early diagnosis. To identify genetic susceptibility markers for this cancer, we carried out a genome-wide association study on 981 individuals with pancreatic cancer (cases) and 1,991 cancer-free controls of Chinese descent using 666,141 autosomal SNPs. Promising associations were replicated in an additional 2,603 pancreatic cancer cases and 2,877 controls recruited from 25 hospitals in 16 provinces or cities in China. We identified five new susceptibility loci at chromosomes 21q21.3, 5p13.1, 21q22.3, 22q13.32 and 10q26.11 ( P = 2.24 × 10 −13 to P = 4.18 × 10 −10 ) in addition to 13q22.1 previously reported in populations of European ancestry. These results advance our understanding of the development of pancreatic cancer and highlight potential targets for the prevention or treatment of this cancer.